A multi-level organizational perspective on the role of HQ in cross-unit collaboration - Nurse, Jeremy (IE University, 2023)
How complex corporations with multidimensional structures create value is a topic of enduring interest and relevance. What is missing from the published literature are in-depth examinations of the nuances found in complex corporate structures, their vertical layers, and particularly with respect to multi-level headquarters (HQ) structures. To fill this gap, this dissertation presents the analysis of a multiple case study in the Massy Group, a large multidivisional, and multinational corporation that operates in the Caribbean, Latin America, and the United States. My research focuses specifically on how corporate parents seek to create value, particularly in relation to how organizational integration is sought in complex corporate structures. Through in-depth interviews with a total of 55 Massy Group insiders as informants across five strategic initiatives that involved different kinds of cross-unit collaboration, I sought insight into two research questions: 1) What is the role of multiple HQ levels in supporting cross-unit collaboration? and 2) How do multiple HQ levels deploy integrative devices to support cross-unit collaboration? In my research, I concluded that both management and oversight at multiple HQ levels are crucial for enabling cross-unit collaboration and elaborated on how the theoretical concepts of integrative devices can manifest as HQ roles. More specifically, the study highlights how the use of authority, communication, and cross-unit structure are important integrative devices that support collaboration within this organizational context. Overall, the findings of this research contribute to a better understanding of the roles and mechanisms through which multiple HQ levels can facilitate cross-unit collaboration in large, diversified multinational firms.
Una perspectiva organizacional multinivel sobre el papel de la sede central en la colaboración entre unidades
Keywords: Estrategia; Gestión financiera; Creación de valor; Gestión Financiera; Producción; Organización de Recursos Humanos